Interpreting panoramic radiographs for beginners - Ghazali, Ahmad Badruddin (2020)
Panoramic radiography is widely used in dentistry and was considered a significant breakthrough as both jaws, together with the dentition, are imaged with a quick and straightforward procedure.1 It has a wide variety of uses requiring broad coverage of the jaws, including traumatic fractures, impacted third molars, dental problems or bony diseases, evaluation of tooth development, temporomandibular joint pain and other anomalies.2 Distinct soft tissue, bony landmarks from midfacial to the chin region as well as the teeth can be seen in the radiograph.3 Interpreting panoramic radiographs may be tricky especially for beginners, and this article will discuss the steps needed to read the wide sized black, white and grey images.